2019
DOI: 10.1007/s12028-019-00789-2
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Brain Cooling Without Core Temperature Reduction in Pigs Using a Novel Nasopharyngeal Method: An Effectiveness and Safety Study

Abstract: Background: Acute brain lesions constitute an alarming public health concern. Neuroprotective therapies have been implemented to stabilize, prevent, or reduce brain lesions, thus improving neurological outcomes and survival rates. Hypothermia is the most effective approach, mainly attributed to the reduction in cellular metabolic activity. Whole-body cooling is currently implemented by healthcare professionals; however, adverse events are frequent, limiting the potential benefits of therapeutic hypothermia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“… 38 40 Recently, several studies have attempted selective hypothermic methods to exclusively cool brain and maintain systematic temperature generally normal. 41 , 42 We have established a proof of concept of SI-AC in a rodent model. 14 We also showed that rapid induction of brain hypothermia with a localized coolant infusion mitigated the degree of brain infarction and neurological deficits with little disturbances to major physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“… 38 40 Recently, several studies have attempted selective hypothermic methods to exclusively cool brain and maintain systematic temperature generally normal. 41 , 42 We have established a proof of concept of SI-AC in a rodent model. 14 We also showed that rapid induction of brain hypothermia with a localized coolant infusion mitigated the degree of brain infarction and neurological deficits with little disturbances to major physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…65 Conversely, a swine model did demonstrate the safety and efficacy of a new nasopharyngeal cooling catheter, with no reported device-related adverse effects. 66 Further research is required to confirm the advantage of cooling the brain (as well as the body) through the upper airway over other cooling methods.…”
Section: Selective Brain Coolingmentioning
confidence: 99%